EFFECTIVENESS OF INTENSIVE TRAINING OF MILITARY SPECIAL EDUCATIONAL INSTITUTIONS - SARIYEVA ASEMGUL KYDYRBAEVNA (Reviews of Modern Science, 2025)
The article provides intensive methods of teaching foreign languages, intensive methods of teaching a foreign language - mastering a foreign language in a limited time, developing and understanding oral language skills, the article defines their methodological value in terms of their effectiveness and effectiveness in teaching foreign languages